One- vs. Three-Fraction Pancreatic Stereotactic Body Radiation Therapy for Pancreatic Carcinoma: Single Institution Retrospective Review - Sutera, Philip Anthony; Bernard, Mark E.; Gill, Beant S.; Harper, Kamran K.; Quan, Kimmen; Bahary, Nathan; Burton, Steven A.; Zeh, Herbert; Heron, Dwight E. (Frontiers in Oncology, 2017)
Background/introduction Early reports of stereotactic body radiation therapy (SBRT) for pancreatic ductal adenocarcinoma (PDAC) used single fraction, but eventually shifted to multifraction regimens. We conducted a single institution review of our patients treated with single- or multifraction SBRT to determine whether any outcome differences existed. Methods and materials Patients treated with SBRT in any setting for PDAC at our facility were included, from 2004 to 2014. Overall survival (OS), local control (LC), regional control (RC), distant metastasis (DM), and late grade 3 or greater radiation toxicities from the time of SBRT were calculated using Kaplan–Meier estimation to either the date of last follow-up/death or local/regional/distant failure. Results We identified 289 patients (291 lesions) with pathologically confirmed PDAC. Median age was 69 (range, 33–90) years. Median gross tumor volume was 12.3 (8.6–21.3) cm3 and planning target volume 17.9 (12–27) cm3. Single fraction was used in 90 (30.9%) and multifraction in 201 (69.1%) lesions. At a median follow-up of 17.3 months (IQR 10.1–29.3 months), the median survival for the entire cohort 17.8 months with a 2-year OS of 35.3%. Univariate analysis showed multifraction schemes to have a higher 2-year OS 30.5% vs. 37.5% (p = 0.019), it did not hold significance on MVA. Multifractionation schemes were found to have a higher LC on MVA (HR = 0.53, 95% CI, 0.33–0.85, p = 0.009). At 2 years, late grade 3+ toxicity was 2.5%. Post-SBRT CA19-9 was found on MVA to be a prognostic factor for OS (HR = 1.01, 95% CI, 1.01–1.01, p = 0.009), RC (HR = 1.01, 95% CI 1.01–1.01, p = 0.02), and DM (HR = 1.01, 95% CI, 1.01–1.01, p = 0.001). Conclusion Our single institution retrospective review is the largest to date comparing single and multifraction SBRT and the first to show multifraction regimen SBRT to have a higher LC than single fractionation. Additionally, we show low rates of severe late toxicity with SBRT.